Synergistic chemopreventive effect of allyl isothiocyanate and sulforaphane on non-small cell lung carcinoma cells. Issue 2 (29th January 2019) - Rakariyatham, Kanyasiri; Yang, Xiao; Gao, Zili; Song, Mingyue; Han, Yanhui; Chen, Xianggui; Xiao, Hang
Abstract : Combination of allyl isothiocyanate and sulforaphane produced a synergistic inhibition on lung cancer cell growth. Abstract : Isothiocyanates from cruciferous vegetables are known for their potential anti-carcinogenic activities. These isothiocyanates are frequently consumed together as part of a regular diet, but their combined effects on carcinogenesis have not been well studied. Herein, we tested the hypothesis that combination of two isothiocyanates, i.e. allyl isothiocyanate and sulforaphane, produced a synergy in inhibiting the growth of A549 lung cancer cells. Our results showed that the combination treatment led to a stronger growth inhibition than the singular treatment. Isobologram analysis proved that the enhanced inhibitory effect of the combination treatment was synergistic. Flow cytometry demonstrated that the combination treatment caused more extensive cell cycle arrest and apoptosis than the singular treatment with modified expression of key proteins regulating these cellular processes. The combined treatment resulted in the production of intracellular reactive oxygen species, which might contribute to the inhibitory effects on cancer cells. Moreover, a synergy between allyl isothiocyanate and sulforaphane was also observed in anti-cell migration. Collectively, our results have demonstrated the potential of different isothiocyanates used in combination to produce enhanced protective effects against carcinogenesis.